Morphology, Disease and Pest Infestation Variations in Different Betel Vine Genotypes: Production, Nutritional Evaluation, and Product Development Using Jackfruit Jam - Obaidullah, A J M; Naher, S; Islam, M R; Rahman, M A; Mashuk, H A; Alam, M A (Bangladesh Journal of Agriculture, 2025)
Betel vine is one of the important cash crops that gaining popularity in recent time in Bangladesh. In the varietal improvement program, collection and evaluation of the germplasm from different parts of the country is crucial. Thus, the present experiment was conducted to collect, characterize and evaluate betel vine genotypes at Spices Research Centre, Shibganj, Bogura during 2021-2022 and 2022-2023. A total of 30 genotypes of betel leaf were collected from different places for characterization and evaluation. The experimental plots were arranged in a Randomized Complete Block Design (RCBD) with three replications. Data were collected three times annually during leaf harvests, encompassed a range of morphological traits. Four genotypes (BL0027, BL0018, BL0024 and BL0030) were found promising in terms of leaf quality and less susceptible to disease and pest infestation. This study is important for betel vine breeding, offering insights into its variation and potential for tailored cultivation. Future research should explore the morphological and environmental factors that affect these traits to improve betel vine cultivation and management. Bangladesh J. Agri. 2025, 50(1): 36-46